Deadwood position matters: Diversity and biomass of saproxylic beetles in a temperate beech forest - Václav Zumr; Oto Nakládal; Josef Gallo; Jiří Remeš (Forest Ecosystems)
Deadwood plays a key role for biodiversity in forests. A significant number of beetles from this group are currently listed as endangered in the Red List. In addition to other management recommendations, there have been recent efforts to enrich stands with dead wood to promote biodiversity. An important parameter for forestry enterprises is the optimization of these interventions. The study investigated the abundance, species richness, gamma diversity, conservation value and biomass of saproxylic beetles in natural forests using window traps. A total of 89 traps were used for saproxylic beetle monitoring, of which 29 were placed on lying logs, 30 on snags and 30 as controls in forest stand space. A total of 35,011 beetles were recorded in 564 species (61 families). Notably, 20,515 of these belong to saproxylic beetles (59%) in 311 species (55%), with 62 classified as Red-List species (20%). In the group of ‘all saproxylic beetles’, the results indicate that α diversity and γ diversity (q ​= ​0) remain consistent across various deadwood types, while β diversity showed significant differences. Significant differences were found in the Red-List species group, where α diversity and γ diversity differed, with higher values observed in snags. Rarefaction based total species richness of site was estimated to be 391 species, including 74 Red-Listed species. Comparing the sample coverage of the studied stand categories showed that all saproxylic species exhibit a pronounced preference for inhabiting areas featuring lying logs. Conversely, Red-List species mainly inhabit snags, with β diversity being more similar to snags and forest stand space. Notably, both the conservation value (weighted average by conservation status) and beetle biomass are significantly highest in snags, whereas stand space shows the lowest values across all measured saproxylic beetle indices. Furthermore, the use of traps set on the poles in forest stand space resulted in an underestimation of the actual stand richness by 20%–25%. Our results support the conclusion that snags are indispensable features in beech forests, playing a key role in promoting high species diversity, especially among Red-List species, and supporting the biomass of saproxylic beetles. Consequently, it becomes crucial to incorporate a higher percentage of standing deadwood in managed forests or actively create equivalent environments by introducing high stumps.